VEP and ERP measurement for Amplitude and Latency in one Metric - Jaya Kumar, Jaya Vicknessvar (Universiti Teknologi PETRONAS, 2021)
The ever growing research in neuroscience especially in EEG is wide and varied. As for the research being done in event related potentials (ERP), many aspects of the stimuli are being tested and experimented to see the response it has on the brain electrical signals. One of the widely studied part of ERP is visually evoked potentials (VEP). As the parameters for the measured amplitude and latency lie in the same domain, it is proposed that there is a possibility to be able to combine both the parameters into a single metric. This is the main problem statement for this paper. The reasoning behind as to why it would be beneficial to combine both the parameters into a single metric is so that it would make future research on VEPs much more simpler to analyze. Current research has yet to tackle this problem one way or another. The data for the VEPs are collected from open sources online. This research would include data analyzing and mathematical modelling.